LATTICE BOLTZMANN STUDY OF HYDRODYNAMIC SPINODAL DECOMPOSITION - Osborn, W; Orlandini, E; Swift, M; Yeomans, J; Banavar, J (1995)
We study both the dynamics of dissolution of an equilibrium interface and phase separation in two-dimensional fluids using lattice Boltzmann simulations. Results for a liquid-gas system and a binary fluid are compared. For symmetric quenches in the liquid-gas system, single-phase domains grow like t, where =12 for high viscosities (corresponding to early times), crossing over to =23 for low viscosities (later times). For a binary fluid the crossover is between =13 and =23. This behavior is compared to that for nonsymmetric quenches. © 1995 The American Physical Society.